ANALISIS PENGARUH VARIASI STIMULUS GURU TERHADAP AKTIVITAS BELAJAR SISWA PADA PEMBELAJARAN BAHASA INDONESIA DI SMA NEGERI 9 KUPANG - Haba Laki, Irnanda P; Djuli, Labu; Djokaho, Margareta P.E. (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2024)
This research aims to find out how much influence the variation in stimulus provided by Indonesian language subject teachers have on student learning activities in the Indonesian language learning process in the classroom. This research study was motivated by the low level of student learning activity when learning Indonesian in class, indicated by the existence of student who were lazy to answer the teacher’s questions directly, did not want to ask questions when they did not understand the material that had been explained and were lazy about reading books. This research uses a quantitave type of research, using ex post facto research methods. The population in this study was 85 people and one Indonesian language subject teacher. The sampling technique used is a saturated sample. Data collection techniques use interviews, questionnaires and documentation. Data analysis techniques use descriptive analysis and multiple linear regression. The results of the research show that it has a significant effect on students’ learning activities in Indonesian language learning for class the conclusion of this research is that there is a significant influence or partially accepted Ha on student learning activities in learning Indonesian in class, namely that variations in teacher stimulus influence student learning activities in learning Indonesian in Class XII MIA 1 dan MIA 2 at SMA Negeri 9 Kota Kupang. So the role of the teacher is very important in implementing various variations of good and appropriate stimuli for the continuity of the learning process in the classroom, especially in Indonesian language learning.